Radical Surgical Excision and Use of Axillary Flap for Intractable Axillary Hidradenitis Suppurativa - Momotaz, Munny; Kalam, Abul; Khondoker, Md Sazzad; Sumi, Sharmin Akter (Journal of Surgical Sciences, 2021)
Background: Current treatments for hidradenitis suppurativa (HS) include prolonged courses of antibiotics, retinoids, immunosuppressants, and biologics. Severe cases that are resistant to prolonged medical treatment pose a therapeutic challenge. We propose radical excision and reconstruction with axillary flap as a treatment option for such cases. Objectives: The purpose of the study was to see the outcome after radical surgical excision and coverage with axillary flap for intractable Hidradenitis suppurativa. Methods: This prospective observational study was carried out from July, 2014 to June,2016. Patients admitted at the Plastic Surgery Department of Dhaka Medical College Hospital with intractable Hydradenitis suppurativa were included the study population. Result:Among 20 cases, 12 cases were female and 8 cases were male. Maximum dimension of the soft tissue defect was 15x6.5 cm2 = (97.5 cm2). Maximum dimension of the flap was 17x7 cm2 = (119 cm2).Flap survived completely with minimum donor site morbidity. Result of reconstruction of 90% of the patients exhibited excellent outcome. In 10% patient’s outcome was considered good. Conclusion:With a suitable flap coverage option, the management paradigm of intractable Hydradenitis Suppurativa should shift from prolonged medical treatment to allowdecisive radical excision, which will improve the quality of life for patients. Axilary flap is the flap of choice to cover the defect. Journal of Surgical Sciences (2020) Vol. 24 (2) : 51-56